State Authority in Utilization of Village Fund in ‘Susukan’ Village, Bogor, West Java - Irfan Ridwan Maksum; Alisa Sangaji (Journal of Public Administration and Local Governance, 2019)
This study was aimed to analyze the implementation of the policy on utilization of village fund at Susukan village, Bogor regency, and factors affecting the implementation. The study used qualitative method resulting in descriptive data collected from analysis of documents, observation, and in-depth interview with several sources of information. The results showed several important facts such as low participation from villagers who were less proactive in utilizing the fund and the limitation of human resources as the program executors were the main inhibitors to the implementation of the village fund utilization at Susukan village. State authority was used as the model in utilization of the village fund at Susukan village and several factors were found to be the most affecting factors for the implementation of the policy, which were basic requirements and objective of the policy, resources, characteristics of the policy executors, and social characteristics of the local people.